eHealth, digital information and technology use of men with prostate cancer - Stuart R Jackson; Paul Yu; Steven Sowter; Stefano Occhipinti; Suzanne Chambers; Scott Leslie; Manish I Patel (Digital Health)
Background The investigation of digital information sources and technologies specifically used by men with prostate cancer is scarce. This study seeks to address current gaps in the literature by investigating prostate cancer–specific internet and technology use by men with prostate cancer and factors associated with this use. Methods Cross-sectional surveys were conducted in three Australian urology clinics (local in Sydney, Western Sydney and Murrumbidgee) in 2023. Data analysis included descriptive and bivariate analysis. Chi square tests of independence, Mann–Whitney U tests and Fischer exact tests were used to assess demographic, prostate cancer-specific and psychometric variables with prostate cancer-specific usage of each website, social media and technology type. Results A total of 349 men responded. Mean age of respondents was 69.6 years (SD 7.8). 74.5% ( n = 260) had undergone radical prostatectomy, while 10% ( n = 35) reported locally advanced/metastatic disease. Information websites were used by 77.7% ( n = 271) of men. Social media was used by 37% ( n = 129), and total internet use was 79.1% ( n = 276). Younger age, higher education and higher income were commonly associated with a greater extent of use of information source and technology types. High variability in usage and factor association was demonstrated between and within analysed group categories. Conclusions Men with prostate cancer use a broad variety of digital information sources and technologies to access prostate cancer information at a higher rate than ever before. This work stresses the significant variability in the extent of use which men demonstrate among these resources and the factors which may play a role in this behaviour.